2012
DOI: 10.1051/0004-6361/201218903
|View full text |Cite
|
Sign up to set email alerts
|

Confronting a solar irradiance reconstruction with solar and stellar data

Abstract: Context. A recent paper by Shapiro and colleagues (2011, A&A, 529, A67) reconstructs spectral and total irradiance variations of the Sun during the holocene. Aims. In this note, we comment on why their methodology leads to large (0.5%) variations in the solar TSI on century-long time scales, in stark contrast to other reconstructions which have < ∼ 0.1% variations. Methods. We examine the amplitude of the irradiance variations from the point of view of both solar and stellar data. Results. Shapiro et al.'s lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 36 publications
4
66
0
Order By: Relevance
“…Recently, Shapiro et al (2011) and Judge et al (2012) also proposed TSI models based a comparison between solar irradiance reconstructions and sunlike-stellar data that show a TSI secular variability at least 3-to-6 times greater than Lean's TSI proxy, similar to those proposed by Hoyt and Schatten (1993). The Shapiro model also predicts a small TSI increase between the solar minima of 1986 and 1996, that is more consistent with the ACRIM 1980-2000 upward TSI pattern and contradicts PMOD.…”
Section: Resultsmentioning
confidence: 82%
“…Recently, Shapiro et al (2011) and Judge et al (2012) also proposed TSI models based a comparison between solar irradiance reconstructions and sunlike-stellar data that show a TSI secular variability at least 3-to-6 times greater than Lean's TSI proxy, similar to those proposed by Hoyt and Schatten (1993). The Shapiro model also predicts a small TSI increase between the solar minima of 1986 and 1996, that is more consistent with the ACRIM 1980-2000 upward TSI pattern and contradicts PMOD.…”
Section: Resultsmentioning
confidence: 82%
“…Solanki et al 2013) but it is presently unclear whether this field can contribute to the irradiance variability on the centennial timescale (see e.g. discussion in Judge et al 2012, and references therein). The ambiguity associated with this effect is an additional source of uncertainty in our estimate of the contributions of molecular and atomic lines to irradiance variability on the centennial timescale.…”
Section: Spectral Irradiance Variability On Different Timescalesmentioning
confidence: 99%
“…The stronger reductions in TSI have been criticized as being too large (Feulner, 2011), but here we regard these estimates as an absolute lower bound in TSI. Judge et al (2012) found the Shapiro et al (2011) estimates to be within bounds set by current stellar data, however, likely have over-estimated quiet-Sun irradiance variations by about a factor of two, based upon a re-analysis of sub-mm data from the James Clerk Maxwell telescope. This is the basis for the WD and WDR scenarios 10 employed here.…”
Section: Methodsmentioning
confidence: 66%